1999
DOI: 10.1002/(sici)1097-0185(19991201)256:4<366::aid-ar4>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Distinct spatial and temporal distributions of aggrecan and versican in the embryonic chick heart

Abstract: Although chondroitin sulfate proteoglycans (CSPGs) are major components of the embryonic extracellular matrix, little attention has been paid to specific CSPGs in early heart development, in part because appropriate antibodies were not available. Therefore we prepared specific polyclonal antibodies against chicken aggrecan, versican, neurocan, and phosphacan. Western blotting and immunohistochemical studies revealed the presence of aggrecan and versican in stages 12-21 chicken embryo hearts in distinctive spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 53 publications
3
43
0
Order By: Relevance
“…Robust HA staining persisted in the AV cushions from the early cushion-forming stage (HH stage-17) to the cushion maturation stage (HH stage-29). Consistent with a previous report indicating declining mRNA expression of aggrecan in the heart after HH stage-20 [26], we found that aggrecan protein was most intensely expressed at HH stage-24 but was less abundantly expressed at HH stage-29 in the heart. …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Robust HA staining persisted in the AV cushions from the early cushion-forming stage (HH stage-17) to the cushion maturation stage (HH stage-29). Consistent with a previous report indicating declining mRNA expression of aggrecan in the heart after HH stage-20 [26], we found that aggrecan protein was most intensely expressed at HH stage-24 but was less abundantly expressed at HH stage-29 in the heart. …”
Section: Resultssupporting
confidence: 92%
“…HA localization was histochemically detected with hyaluronan binding protein (HABP) following the protocol described previously [25]. Production and specificity of the anti-chick versican and anti-chick aggrecan antibodies were described previously [26]. At the early stage of cardiac cushion expansion (HH stage-17), intense immunostaining of versican was observed in the basement membrane of the endocardial side of myocardium, most prominently at the distal end of the cardiac inlet and outlet (arrows in Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…5M,N). Overall, this expression pattern of zebrafish versican was equivalent to that of other vertebrate versican (Mjaatvedt et al, 1998;Zanin et al, 1999;Perissinotto et al, 2000).…”
Section: Expression Of Dermacan Mrna During Embryogenesismentioning
confidence: 65%
“…The data described here supports the hypothesis that TBX20 acts upstream of aggrecan. Aggrecan is one of the main chondroitin sulfate proteoglycan constituents of the spongiosa layer in avian valves, and is required to withstand compressive forces against blood flow [32], [43], and reportedly has a role in valve cell differentiation [44], [64].…”
Section: Discussionmentioning
confidence: 99%